2019
DOI: 10.1002/oa.2836
|View full text |Cite
|
Sign up to set email alerts
|

Palaeodiet reconstruction inferred by stable isotopes analysis of faunal and human remains at Bronze Age Punta di Zambrone (Calabria, Italy)

Abstract: Recent research has shown that the Bronze Age is a crucial period of dietary changes in Italy. Following this line of enquiry, the paper reports the results of stable isotope analysis (δ 13 C and δ 15 N) of faunal bone collagen as well as of collagen extracted from a few human bones dated to the Recent Bronze Age (13th/12th century BCE) and excavated at the coastal settlement of Punta di Zambrone (PdZ) in Calabria, southern Italy. They constitute the first such data on that period from the Italian south and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
5
1
2
Order By: Relevance
“…For the Bronze Age, we expected substantial differences of isotope values between northern and southern sites because, as is known from the literature, millet was introduced in northern Italy during this period. Contrary to what has been recently proposed by Rumolo et al (2020), it was not regularly consumed in southern Italian communities of the same period (Tafuri et al 2009;Varalli et al 2016a). In northern Italy, Panicum miliaceum cultivation started during the Early Bronze Age, as shown by an increase in the cultivation of this cereal in the Middle/Late Bronze Age at Monte Covolo (Pals and Vorrips 1979) and at Canár (Castiglioni et al 1998;Castelletti et al 2001) and as attested at Terramara di Montale by the archaeological record (Mercuri et al 2006).…”
Section: Southern Italian Bronze Age Sites Vs Central-northern Sitescontrasting
confidence: 90%
See 3 more Smart Citations
“…For the Bronze Age, we expected substantial differences of isotope values between northern and southern sites because, as is known from the literature, millet was introduced in northern Italy during this period. Contrary to what has been recently proposed by Rumolo et al (2020), it was not regularly consumed in southern Italian communities of the same period (Tafuri et al 2009;Varalli et al 2016a). In northern Italy, Panicum miliaceum cultivation started during the Early Bronze Age, as shown by an increase in the cultivation of this cereal in the Middle/Late Bronze Age at Monte Covolo (Pals and Vorrips 1979) and at Canár (Castiglioni et al 1998;Castelletti et al 2001) and as attested at Terramara di Montale by the archaeological record (Mercuri et al 2006).…”
Section: Southern Italian Bronze Age Sites Vs Central-northern Sitescontrasting
confidence: 90%
“…Craig et al 2006;Lai et al 2013). Exceptions to this trend may be represented by the site of Grotta dello Scoglietto in central Italy (Varalli et al 2016a) and Punta di Zambrone in Calabria (Rumolo et al 2020). The latter study has, in our opinion, not fully justified a good collagen quality of the included samples and has not demonstrated that its results may not indicate marine resource consumption by the analysed humans (favouring the interpretation that C 4 plants were consumed at the site).…”
Section: Environmental Comparisonsmentioning
confidence: 71%
See 2 more Smart Citations
“…The sites of Arano, Olmo di Nogara, Mereto, Sedegliano, Gradisca di Codroipo, Lavello, Toppo Daguzzo, Dossetto di Nogara, Bovolone, Fondo Paviani, Gr. Regina Margherita and Punta di Zambrone followed a similar collagen extraction protocol applied to a fragment of cortical bone 25 , 59 , 60 , 62 , 64 . The samples from Gr.…”
Section: Methodsunclassified